Case reportStevens-Johnson syndrome/toxic epidermal necrolysis presumably induced by norfloxacin - Maciejewska, Jolanta; Jankowski, Marek; Zegarska, Barbara; Czajkowski, Rafał (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are rare mucocutaneous, unpredictable, life-threatening drug side reactions. A very rare case of norfloxacin-induced SJS/TEN overlap with uncommon clinical presentation in a patient with a suspected urinary tract infection is reported. The SJS/TEN management with possible treatment capabilities are discussed. In spite of only two previous reports of norfloxacin-induced SJS and TEN we believe that awareness of norfloxacin adverse reactions needs to be raised among prescribers.